2021
DOI: 10.1016/j.ejca.2020.09.030
|View full text |Cite
|
Sign up to set email alerts
|

Real-world evidence of cabozantinib in patients with metastatic renal cell carcinoma: Results from the CABOREAL Early Access Program

Abstract: Background: Real-world data on cabozantinib in metastatic renal cell carcinoma (mRCC) is limited. This study (CABOREAL) reports treatment patterns and outcomes for patients treated with cabozantinib through the French Early Access Program. Patients and methods: This multicentre (n Z 26), observational, retrospective study enrolled patients with mRCC who had received 1 dose of cabozantinib. Overall survival (OS) was estimated using the KaplaneMeier method; subgroups were compared using the log-rank test.A multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 21 publications
4
27
0
1
Order By: Relevance
“…Nearly all patients (99%) received cabozantinib in the second or laterline setting with 41% of patients having had > 3 lines of prior therapy. Consistent with our results, this study revealed a median treatment duration of 7.6 months and a median OS of 14.4 months [16]. In contrast to our analysis, the CABOREAL study did not report response rates or TTF outcomes.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Nearly all patients (99%) received cabozantinib in the second or laterline setting with 41% of patients having had > 3 lines of prior therapy. Consistent with our results, this study revealed a median treatment duration of 7.6 months and a median OS of 14.4 months [16]. In contrast to our analysis, the CABOREAL study did not report response rates or TTF outcomes.…”
Section: Discussionsupporting
confidence: 88%
“…We observed activity of cabozantinib in patients who had previously received ICI, with a DCR of 64% and median OS of 15.8 months (range 10.3 -20.7 months). Similar findings were seen in the METEOR study as well as other retrospective series [16][17][18][19][20]. Importantly, we included patients treated immediately after first-line ICI-based combination therapy (Table 3), which represents a group where data is lacking on the optimal treatment strategy.…”
Section: Discussionmentioning
confidence: 86%
“…The CERES population was more similar to that of CABOREAL (NCT03744585) -the largest study of cabozantinib in a real-world RCC population conducted to date. 20 CABOREAL included patients (n = 410) receiving cabozantinib treatment for RCC via the French Temporary Authorisation for Use (ATU) programme. 20 CCI score was not reported in CABOREAL, but 39.3% of included patients had an ECOG PS of at least 2, and approximately one-third of patients were categorized as having poor-risk IMDC (31.7%) and MSKCC (33.9%) scores.…”
Section: Discussionmentioning
confidence: 99%
“…20 CABOREAL included patients (n = 410) receiving cabozantinib treatment for RCC via the French Temporary Authorisation for Use (ATU) programme. 20 CCI score was not reported in CABOREAL, but 39.3% of included patients had an ECOG PS of at least 2, and approximately one-third of patients were categorized as having poor-risk IMDC (31.7%) and MSKCC (33.9%) scores. 20 Estimated median OS was slightly longer in CABOREAL than in CERES (14.4 versus 10.8 months, respectively), 20 but published real-world estimates for OS vary widely for aRCC populations (7.7-23.7 months) 11,21,22 because of key differences in the design and eligibility for the associated studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation